تأثير الغش على خوارزميات بناء أشجار التغطية في الشبكات التطبيقية متعددة البث - مثنى القبيلي (Tishreen University, 2016)
Application-Level Multicast (ALM) has been proposed as an alternative solution to overcome the lack of deployment of the IP Multicast group communication model. It builds an overlay tree consisting of end-to-end unicast connections between end-hosts based on the collaboration of group members with each other. The efficiency of the constructed overlay tree depends entirely on the honesty and on the cooperation of all participating members. However such behaviour can not be guaranteed and some selfish and non-cooperative nodes may take profit from the honesty of other members in the overlay. Recently, many researchers have been investigating the impact of selfishness of nodes in the overlay multicast. Our contribution in this paper is to describe in detail the basic algorithms used to construct the overlay tree, and evaluate the impact of cheating nodes on the stability and on the performance of constructed overlay tree using these algorithms. تم اقتراح الشبكات التطبيقية متعددة البث كحل فعال لتجاوز مشكلة انتشار نموذج اتصال البث المجموعاتي. تبني هذه الشبكة شجرة تغطية مؤلفة من اتصالات نهاية إلى نهاية أحادية البث اعتماداً على تعاون أعضاء المجموعة مع بعضهم البعض. وتعتمد فعالية الشجرة المبنية بشكل أساسي على صدق وتعاون كل الأعضاء المشكلين لها، لكن من الصعب ضمان مثل هذا السلوك عموماً، حيث يمكن أن تستفيد بعض العقد الأنانية وغير المتعاونة من إخلاص العقد الأخرى ضمن الشجرة. حديثاً، درس العديد من الباحثين تأثير العقد الأنانية في الشبكات التطبيقية متعددة البث. تم في هذا البحث وصف تفصيلي للخوارزميات الأساسية المستخدمة في بناء شجرة التغطية، وتقييم تأثير العقد الغشاشة على استقرار وأداء شجرة التغطية المبنية باستخدام هذه الخوارزميات.